Hamlet Revision: Bhardwaj's Haider as Crossmapping and Contact Zone. (28th December 2020) - Hoydis, Julia
Abstract: Completing his trilogy of adaptations of Shakespearean tragedies, Indian director Vishal Bhardwaj's film Haider (2014) tackles Hamlet . A generic fusion of realist drama, Bollywood movie, and espionage thriller, the film intersects the Elizabethan source text's revenge plot with intertextual references to journalist Basharat Peer's contemporary war memoir Curfewed Nights (2011), detailing the realities in insurgency-torn Kashmir in the 1990s. Taking its cue from the film's controversial reception, which runs the gamut from censorship, appraisals, and criticism that Indian film does not need the 'crutch' of Hamlet to claim attention, this article explores questions about border-crossing, violence, and reconciliation raised on the level of form and content. Haider presents an adaptation of not one but two source texts: one 'global' and one 'local'. The result, this article argues, is astonishingly harmonious and the contested metaphors of adaptation theory and global Shakespeare studies, such as 'appropriation' or 'indigenization', apply less to it than that of a transcultural 'contact zone' (Pratt, Mary Louise. Imperial Eyes. Travel Writing and Transculturation, 2nd. ed. London and New York: Routledge, 2008) and of a 'crossmapping' (Bronfen, Elisabeth. Crossmappings. On Visual Culture . London and New York: I.B. Tauris, 2018). By placing greater emphasis on communality and having the ending turn from revenge to forgiveness, Haider interrogates the transcultural appeal of Hamlet, drawing attention to histories of violent conflict. It also reveals a revisionist agenda that captures both hidden political realities and a haunting refiguration of Shakespeare.